PEMBUATAN BIOSORBEN DARI BIJI PEPAYA (Carica papaya L) UNTUK PENYERAPAN ZAT WARNA - Siswarni MZ, Lara Indra Ranita, Dandri Safitri (Jurnal Teknik Kimia USU, 2017)
Biosorbent is a material that has a pore - pore lot, where the adsorption process can take place on the pore walls or occur in certain regions of the particles. Preparation from papaya seeds biosorbent using H2SO4 as an activator, and then used as a textile dye absorption, namely methyl orange, methyl violet and methyl red. This study aims to determine the optimum conditions in the manufacturing biosorbent from papaya seeds. Analysis is iodine number, surface area, and test the ability of sarap to dyes (methyl orange, methyl violet and methyl red). In the manufacture biosorbent of this papaya seeds, the method used is chemical activation process. This study uses papaya seeds as raw material and sulfuric acid as an activator. The concentration of sulfuric acid used 5%, 7%, 10% and the drying time of 30 minutes, 60 minutes, 90 minutes, and 120 minutes. Biosorbent mass of 0.5 g (2.5% of 20 ml), 1.0 g (5% of 20 ml) and 1.5 g (7.5% of 20 ml) with adsorption time of 20 minutes, 30 minutes, and 40 minutes for the absorption of the dye. The results showed the highest iodine gained 482.22 mg / g on the drying time of 120 minutes and a sulfuric acid concentration of 10% and the highest surface area was obtained 33.43556 m2 / g on the drying time of 120 minutes and a sulfuric acid concentration of 10%. The analysis results of the adsorption capacity for methyl violet dye that is 9.547 mg / g on biosorbent mass of 1.0 g and the adsorption time of 40 minutes..